Uncomplicated Peptic Ulcer Disease and Its Impact on Haematological Parameters - Ahmed, Mohammad Nesar Uddin; Nabi, Quazi Md Rashid Un; Sultana, Sharmeen; Chowdhury, Md Rashed Alam; Ali, Md Omar; Rukunuzzaman, Muhammed (Journal of Armed Forces Medical College, Bangladesh, 2024)
Background: Peptic ulcer disease (PUD) is one of the most common diseases consisting of gastric and duodenal ulcers affecting the gastrointestinal tract of many people of the world which may affect haematological parameters of the patients. Objective: To explore the impact of uncomplicated PUD on haematological parameters. Methods: This observational study was based on data obtained from the Department of Medicine (Gastroenterology) of Jahurul Islam Medical College Hospital (JIMCH), Bajitpur, Kishoregonj from May 2013 to October 2013. A total of 156 participants; 77 uncomplicated PUD patients (39 females and 38 males) and 79 healthy adults as control groups (40 females and 39 males) were included in this study. Subjects visiting the outpatient department of Medicine (Gastroenterology) with epigastric symptoms between the age group of 25 and 60 years who underwent upper gastrointestinal endoscopy were included in the study (with diagnosed uncomplicated PUD). Moreover, blood samples of all participants were taken for biochemical analysis and complete blood parameters were evaluated in the hematology laboratory of JIMCH. All data were expressed as mean±SD. For statistical analysis, Chisquare test (χ2) was used to compare categorical variables. An independent sample ‘t’ test was used to compare normally distributed variables between two groups. Results: The mean values of Hgb, RBC, Hct, MCV, MCH, MCHC were observed to be significantly lower in uncomplicated PUD when compared to control group. However, the mean values of neutrophil count, monocyte count, neutrophil-to-lymphocyte ratio (NLR) and monocyteto-lymphocyte ratio (MLR) were significantly higher in uncomplicated PUD patients than that of the control group. On the other hand, mean values of platelet count and (platelet-to-lymphocyte ratio) PLR were lower in uncomplicated PUD patients in comparison to control group which were statistically non-significant. Conclusion: In summary, findings of the study reveal that uncomplicated PUD may cause reduction of RBC parameters and may increase the mean value of peripheral white blood cell counts for neutrophils, monocytes, platelets; NLR, MLR and PLR also may increase. Therefore, hematological parameters of uncomplicated PUD show a significant variation that should be considered for proper diagnosis and management of PUD. JAFMC Bangladesh, Vol 20, No 1 (June) 2024:22-25